Judging homicide defendants by their brains: an empirical study on the use of neuroscience in homicide trials in Slovenia. Issue 1 (25th April 2019) - Hafner, Miha
Abstract: This paper presents a study that analyses all available homicide trials in Slovenia between 1991 and 2015 for neuro-evidence. Almost every fifth case discusses neuroscience. The most prevalent type of neuro-evidence is neuro-psychological testing, less common are structural neuroimaging and electroencephalography, while we discovered no use of functional neuroimaging. The two largest categories of neurological conditions suffered by defendants are traumatic brain injury and brain damage due to long-term alcohol and drug abuse. When presented, neuro-evidence affected courts' decisions in 85% of trials (15% of all tried homicide cases) and had an impact on the criminal sentence or another outcome of the trial in 79% of cases. By far most often neuro-evidence affects decisions regarding criminal capacity, ie insanity and (substantially) diminished capacity, which, in turn, strongly reflects in criminal sanctions. Neuroscience information is typically used to mitigate or even reduce the sentence, but never as an aggravating circumstance. It is also frequently utilized to support decisions about medical security measures (compulsory psychiatric treatment). This study further suggests that the double-edged sword of neuroscience is an elusive concept and that the mechanism by which neuroscience affects courts' decisions in civil-law systems is different from the one in common-law jurisdictions.